Natural and anthropogenic noise increase vigilance and decrease foraging behaviors in song sparrows. (15th December 2021) - Sweet, K A; Sweet, B P; Gomes, D G E; Francis, C D; Barber, J R
Abstract: Animals glean information about risk from their habitat. The acoustic environment is one such source of information, and is an important, yet understudied ecological axis. Although anthropogenic noise has become recently ubiquitous, risk mitigation behaviors have likely been shaped by natural noise over millennia. Listening animals have been shown to increase vigilance and decrease foraging in both natural and anthropogenic noise. However, direct comparisons could be informative to conservation and understanding evolutionary drivers of behavior in noise. Here, we used 27 song sparrows ( Melospiza melodia ) and 148 laboratory behavioral trials to assess foraging and vigilance behavior in both anthropogenic and natural noise sources. Using five acoustic environments (playbacks of roadway traffic, a whitewater river, a whitewater river shifted upwards in frequency, a river with the amplitude modulation of roadway traffic, and an ambient control), we attempt to parse out the acoustic characteristics that make a foraging habitat risky. We found that sparrows increased vigilance or decreased foraging in 4 of 6 behaviors when foraging in higher sound levels regardless of the noise source or variation in frequency and amplitude modulation. These responses may help explain previously reported declines in abundance of song sparrows exposed to playback of intense river noise. Our results imply that natural soundscapes have likely shaped behavior long before anthropogenic noise, and that high sound levels negatively affect the foraging-vigilance trade-off in most intense acoustic environments. Given the ever-increasing footprint of noise pollution, these results imply potential negative consequences for bird populations. Abstract : Song sparrows decrease foraging and increase vigilance behavior in high background sound levels, regardless of the noise source. Both roadway traffic noise and naturally-occurring river noise engender similar changes in behavior. These results suggest that noisy environments, natural and human-created, alter important risk-management behaviors in sparrows and possibly other birds.